PENGARUH KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI DI BEI - Tambalean, Friko Allan Kevin; Manossoh, Hendrik; Runtu, Treesje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The main objective of a business company is to increase the company value shown by the stock price, but the agency conflict can be an obstacle to achieving it. Managerial ownership and institutional ownership are expected to reduce the negative impact of the conflict. This study aims to determine the influence of managerial and institutional ownership on company value. Managerial ownership and institutional ownership measured by percentage of the share ownership of management and institutions in the company. Company value measured by Price to Book Value ratio. This study was conducted by taking a sample of 60 companies in 2016 and 2017. The result of this study shows that managerial ownership do not affect the company value and institutional ownership do not affect the company value.Keywords: Managerial Ownership, Institutional Ownership, Company value